2021
DOI: 10.5109/4480721
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Conceptual Design Approach of Food Waste Composter Design

Abstract: This paper reports the conceptual design of a household kitchen food waste composter. Several conceptual approaches, such as Quality Function Deployment (QFD), Concept Generation, and Concept of Evaluation using PUGH Method are implemented. The component selection is applied using House of Quality method, and the final design is presented and selected using PUGH Method. Design 1 is selected as the best composter design. The material selection and the cost of the components are also presented. The conceptual de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…This is because, A3 has a 'screened' 'trash arresting area' while It can be observed that many SVs can be obtained from the morphological matrix. Using the prevalent method of random selection of few SVs for evaluation and selection of preliminary design 13) , the design space expansion which is the main advantage of using the morphological matrix is not exploited. By random selection of few concepts many feasible concepts are neglected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because, A3 has a 'screened' 'trash arresting area' while It can be observed that many SVs can be obtained from the morphological matrix. Using the prevalent method of random selection of few SVs for evaluation and selection of preliminary design 13) , the design space expansion which is the main advantage of using the morphological matrix is not exploited. By random selection of few concepts many feasible concepts are neglected.…”
Section: Discussionmentioning
confidence: 99%
“…It comprises of an arrangement of subfunctions and their respective SPs in a matrix form 5) . The alterative SPs can be represented using drawings 13) or writings 11) . In the morphological matrix in Table 1, F1 to Fr represent the subfunctions, while their respective SPs are represented as A1 to As, B1 to Bs and so on.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-treatment of selected feedstock materials done by heat treatment method which is drying process. Drying feedstock material by oven at temperature 40 ⁰C within 1x24 hours 19,20) . These was done to reduce the water content inside feedstock material.…”
Section: Methodsmentioning
confidence: 99%
“…In anaerobic digestion whereas the process with the absence or limited supply of oxygen 13) , hydrogen is produced as a side-product in the acidogenic step but in a low yield. Dark fermentation was used to increase hydrogen production, although the implementation in commercial scale was still challenging 14).…”
Section: Introductionmentioning
confidence: 99%